One-person households in India - Dommaraju, Premchand (2015)
Objective: The objectives of this article are: 1) to estimate the prevalence of one-person households in India; 2) to examine the demographic, social and economic characteristics of these households, and 3) to analyse the determinants of one-person households. Methods: Data from the Indian censuses are used to gauge the prevalence of one-person households. In addition, data from the third round of District Level Household and Facility Survey (DLHS-3), a large and nationally representative data, are used to examine the characteristics of one-person households and to estimate the odds of staying in such households. Results: The prevalence of one-person households in India is low compared to that in other parts of Asia. While the prevalence of OPH is low, the number of such households is large, and expected to grow in the next few decades. The results presented reveal important social, economic and demographic differences between one-person and multi-person households. Elderly females and young migrants who live alone are potential vulnerable groups. The results are situated within the socio-cultural and demographic contexts of India.